Awareness among Breastfeeding Women Regarding Herbal Medicine Use in Primary Health Care of Tegal, Indonesia - Ike Putri Setyatama; Mohammad Zen Rahfiludin; Meidiana Dwidiyanti; Onny Setiani (Jurnal Promosi Kesehatan Indonesia, 2025)
Background: Exclusive breastfeeding is essential for infant growth and maternal health. However, factors such as low milk production often hinder breastfeeding success. Herbal medicine is commonly used to stimulate milk production, yet awareness of its proper use among breastfeeding mothers remains inconsistent. Limited evidence exists on the factors influencing this awareness, particularly in primary health care settings.Method: A cross-sectional observational study was conducted in March–April 2025 at the Primary Health Care Centers in Tegal Regency, Central Java, Indonesia. A total of 116 breastfeeding mothers were selected using purposive sampling. Data were collected through structured questionnaires covering maternal, child, and family characteristics as well as awareness of herbal medicine use. Data were analyzed using univariate and bivariate methods.Result: Most breastfeeding mothers reported awareness and use of herbal medicine to support milk production. Factors associated with higher awareness included maternal age, employment status, and parental support. Many mothers, however, did not inform health workers about their herbal use. The conclusion is Awareness of herbal medicine use among breastfeeding mothers is influenced by maternal and family factors. Primary health care providers should play a stronger role in improving mothers’ understanding of breastfeeding challenges, appropriate herbal use, and the safety of herbal preparations.